Comparison of prehospital professional accuracy, speed, and interrater reliability of six pediatric triage algorithms. Issue 1 (14th January 2022) - Cheng, Tabitha; Staats, Katherine; Kaji, Amy H.; D'Arcy, Nicole; Niknam, Kian; Donofrio‐Odmann, J. Joelle
Abstract: Objectives: We evaluated prehospital professionals' accuracy, speed, interrater reliability, and impression in a pediatric disaster scenario both without a tool ("No Algorithm"–NA) and with 1 of 5 algorithms: CareFlight (CF), Simple Triage and Rapid Treatment (START) and JumpSTART (J‐START), Pediatric Triage Tape (PTT), Sort, Assess, Life‐saving interventions, Treatment/Transport (SALT), and Sacco Triage Method (STM). Methods: Prehospital professionals received disaster lectures, focusing on 1 triage algorithm. Then they completed a timed tabletop disaster exercise with 25 pediatric victims to measure speed. A predetermined criterion standard was used to assess accuracy of answers. Answers were compared to one another to determine the interrater reliability. Results: One hundred and seven prehospital professionals participated, with 15–28 prehospital professionals in each group. The accuracy was highest for STM (89.3%; 95% confidence interval [CI] 85.7% to 92.2%) and lowest for PTT (67.8%; 95% CI 63.4% to 72.1%). Accuracy of NA and SALT tended toward undertriage (15.8% and 16.3%, respectively). The remaining algorithms tended to overtriage, with PTT having the highest overtriage percentage (25.8%). The 3 fastest algorithms were: CF, SALT, and NA, all taking 5 minutes or less. STM was the slowest. STM demonstrated the highest interrater reliability, whereas CF and SALT demonstrated the lowest interrater reliability. Conclusions: This study demonstrates the most common challenges inherent to mass casualty incident (MCI) triage systems: as accuracy and prehospital professional interrater reliability improve, speed slows. No triage algorithm in our study excelled in all these measures. Additional investigation of these algorithms in larger MCI drills requiring collection of vital signs in real time or during a real MCI event is needed.